2009
DOI: 10.1007/s00128-009-9689-5
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical and Histopathological Evaluation of 2,4-Dichlorophenoxyacetic Acid-Induced Changes in Rat Kidney Cortex

Abstract: This study aims to investigate the effect of 2,4-dichlorophenoxyacetic acid (2,4-D) on rat kidney cortex histology. Oral exposure of rats to 2,4-D for 28 days resulted in decreases in body weight gain and kidney weight. Histological examination showed degeneration in renal corpuscles and podocytes; vacuolization in the glomerulus with disintegration of the basal membrane; tissue edema; vacuolization, cystic dilation and invagination of the basal laminae in the tubular structures; dilation and congestion in ren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
20
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 15 publications
3
20
0
Order By: Relevance
“…Our findings are in accordance with other earlier reports which have attributed the reduction in body and kidney weights due to reluctant food intake [8][9][10]. It is possible that 2,4-D may have suppressed the hunger centers of a central nervous system, resulting in decreased food intake.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Our findings are in accordance with other earlier reports which have attributed the reduction in body and kidney weights due to reluctant food intake [8][9][10]. It is possible that 2,4-D may have suppressed the hunger centers of a central nervous system, resulting in decreased food intake.…”
Section: Discussionsupporting
confidence: 93%
“…Our findings with regard to histopathology of 2,4-D-treated mice show an agreement with the results of Tayeb et al [8] who reported histopathological damage and change in terms of severe glomerular atrophy, glomerular space, and tubular damages in 2,4-D-treated rat kidney. Another histopathological study of 2,4-D-treated rat kidney done by Uyanikgil et al [10] revealed that renal corpuscular degeneration, vacuolization of proximal tubules, and epithelial change in distal tubules also support the observation of the present study.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations